Using VAK Strategy to Improve Writing Skill Recount Text of Tenth Graders of SMA El - Shadai Kota Magelang in the School Year 2018/2019 - Oriza Regina Bekti Hutami (Faculty of Education and Teachers Training, 2020)
Writing is one of the important skill that should be learned by the students in Senior High School besides speaking, listening, and reading. Based on the observation before, this skill was difficult enough to be learned by the tenth graders of SMA El Shadai Kota Magelang. Most of the students still had low mastery of vocabulary and found difficulties in writing English text.There are two objectives of this research. The first one is to know whether the use of Visual, Auditory, Kinesthetic (VAK) Strategy can improve the students’ learning motivation in recount text writing skill. Secondly, it is to know how great the improvement of the students’ recount text writing skill who are taught using VAK Strategy.The type of this research is Classroom Action Research (CAR). It was divided into Pre-Cycle, Cycle I and Cycle II. This subject of the research was the X MIPA of SMA El Shadai Magelang in the school year 2018/2019.Based on the findings, the result of the data showed that there was great improvement of the students’ motivation in learning English. The total improvement of the non-test from Pre-Cycle to Cycle II gradually increased. The students were enthusiastic to improve their writing skill and finding more information about the text. The students’ behavior changed as well as students interest to pay more attention to the teacher’s explanation in teaching learning process also improved.